Perspectives and practices of dietitians with regards to social/mass media use during the transitions from face-to-face to telenutrition in the time of COVID-19: A cross-sectional survey in 10 Arab countries - Bookari, Khlood; Arrish, Jamila; Alkhalaf, Majid M.; Alharbi, Mudi H.; Zaher, Sara; Alotaibi, Hawazin M.; Tayyem, Reema; Al-Awwad, Narmeen; Qasrawi, Radwan; Allehdan, Sabika; Al Sabbah, Haleama; AlMajed, Sana; et al. (Frontiers in Public Health, 2023)
During the COVID-19 pandemic, most healthcare professionals switched from face-to-face clinical encounters to telehealth. This study sought to investigate the dietitians’ perceptions and practices toward the use of social/mass media platforms amid the transition from face-to-face to telenutrition in the time of COVID-19. This cross-sectional study involving a convenient sample of 2,542 dietitians (mean age = 31.7 ± 9.5; females: 88.2%) was launched in 10 Arab countries between November 2020 and January 2021. Data were collected using an online self-administrated questionnaire. Study findings showed that dietitians’ reliance on telenutrition increased by 11% during the pandemic, p = 0.001. Furthermore, 63.0% of them reported adopting telenutrition to cover consultation activities. Instagram was the platform that was most frequently used by 51.7% of dietitians. Dietitians shouldered new difficulties in dispelling nutrition myths during the pandemic (58.2% reported doing so vs. 51.4% pre-pandemic, p < 0.001). Compared to the pre-pandemic period, more dietitians perceived the importance of adopting tele nutrition’s clinical and non-clinical services (86.9% vs. 68.0%, p = 0.001), with 76.6% being confident in this practice. In addition, 90.0% of the participants received no support from their work facilities for social media usage. Following the COVID-19 outbreak, the majority of dietitians (80.0%) observed a rise in public interest in nutrition-related topics, particularly those pertaining to healthy eating habits (p = 0.001), healthy recipes (p = 0.001), nutrition and immunity (p = 0.001), and medical nutrition therapies (p = 0.012). Time constraint was the most prevalent barrier to offering telenutrition for nutrition care (32.1%), whereas leveraging a quick and easy information exchange was the most rewarding benefit for 69.3% of the dietitians. In conclusion, to ensure a consistent provision of nutrition care delivery during the COVID-19 pandemic, dietitians working in Arab countries adopted alternative telenutrition approaches through social/mass media.